URGENSI ASBABUN NUZUL SEBAGAI KONTEKSTUALISASI PEMAHAMAN PESAN AL-QUR’AN GENERASI MUDA - Syifa Syafriani Simatupang Simatupang; Mahmud Arif (Jurnal Al I'jaz, 2025)
This study examines the urgency of learning asbabun nuzul in helping the younger generation understand the messages of the Qur'an contextually and applicably. Asbabun nuzul provides an understanding of the historical and social background of the revelation of Qur'anic verses, thereby facilitating relevant interpretations of these verses in modern contexts. By studying asbabun nuzul, the younger generation can avoid misunderstandings and apply Islamic values in a moderate manner in daily life. This research employs a literature review method to analyze the concept and role of asbabun nuzul. The findings indicate that understanding asbabun nuzul strengthens faith, bridges gaps in religious understanding, and enhances the Qur'an's relevance in addressing modern challenges.